Mammography: psychological experience, and radiographer's attitudes and behaviors that promote women's cooperation - Grilo, Ana Monteiro (2013)
Mammography is the most effective method available for early detection for breast cancer. Routine screening is being associated with better prognostic, such as, earlier stage disease and mortality reduction. However, mammography is not seen by most women as a more diagnostic test, and many women report having experienced some anxiety, pain and discomfort during breast screening process.  Similarly, a high percentage of women failed to conduct regular mammography screening. This article examined the psychological reactions associated with mammography examination and emphasised how radiographers can improve the situation of women attending the breast screening. Radiographer’s intervention such as provision of information before screening, friendly screening atmosphere and empathetic and coping strategies to reduce pain and discomfort and improve power and autonomy in during mammography are also addressed.